The Bi-directional Relationship between Source Characteristics and Message Content - Collins, Peter J.; Hahn, Ulrike; von Gerber, Ylva; Olsson, Erik J. (Frontiers in Psychology, 2018)
Much of what we believe we know, we know through the testimony of others (Coady, 1992). While there has been long-standing evidence that people are sensitive to the characteristics of the sources of testimony, for example in the context of persuasion, researchers have only recently begun to explore the wider implications of source reliability considerations for the nature of our beliefs. Likewise, much remains to be established concerning what factors influence source reliability. In this paper, we examine, both theoretically and empirically, the implications of using message content as a cue to source reliability. We present a set of experiments examining the relationship between source information and message content in people’s responses to simple communications. The results show that people spontaneously revise their beliefs in the reliability of the source on the basis of the expectedness of a source’s claim and, conversely, adjust message impact by perceived reliability, hence source reliability and message content have a bi-directional relationship. The implications are discussed for a variety of psychological, philosophical and political issues such as belief polarization and dual-route models of persuasion.